Spin dynamics of FeGa3−xGex studied by electron spin resonance. (22nd December 2017) - Koo, Bonho; Bader, Kristian; Burkhardt, Ulrich; Baenitz, Michael; Gille, Peter; Sichelschmidt, Jörg
Abstract: The intermetallic semiconductor FeGa3 acquires itinerant ferromagnetism upon electron doping by a partial replacement of Ga with Ge. We studied the electron spin resonance (ESR) of high-quality single crystals of FeGa3− x Ge x for x from 0 up to 0.162 where ferromagnetic order is observed. For x = 0 we observed a well-defined ESR signal, indicating the presence of pre-formed magnetic moments in the semiconducting phase. Upon Ge doping the occurrence of itinerant magnetism clearly affects the ESR properties below ≈40 K, whereas at higher temperatures an ESR signal as seen in FeGa3 prevails independent on the Ge content. The present results show that the ESR of FeGa3− x Ge x is an appropriate and direct tool to investigate the evolution of 3d-based itinerant magnetism.